Komunikasi Strategis Lobi dan Negosiasi dalam Upaya Peredaman Konflik Agraria Desa Pakel, Banyuwangi - Husni, Muhammad Razali; Sanggoleo, Muhammad Fitrah; Doli H., Syahrial; Margaretha S.; Noor H., M. Tamim (Universitas Methodist Indonesia, 2024)
Land is an important part of human life. Therefore, the state as the highest organization is obliged to provide people's agrarian rights. However, until now, agrarian conflicts still haunt the affected communities. An example is Pakel Village, Banyuwangi, where most of the area is still controlled by the colonial plantation authorities and Perhutani. The conflict, which started in 1993, then re-emerged in 2012 and continued in 2017 until now. Until now there has been no clear solution and the state has not been able to fulfill its promise. Neither legally nor has it been able to provide a protective umbrella that can guarantee the Pakel community. This research aims to analyze conflict and how strategic communication can reduce agrarian disputes in Pakel Village. The research is descriptive qualitative type. Data collection techniques in this research were obtained through literature study or library research through journal research article sources and online news. The research results reveal several stages of strategic communication that can be pursued in the process of reducing agrarian conflict, namely: (1) consolidating internal parties related to conflict resolution; (2) conducting mediation involving all parties involved in the conflict; and (3) involving stakeholders in conflict resolution. Consolidation is a communication process, where all parties are involved in high intensity discussions. The mediation process is also part of the communication strategy in resolving agrarian conflicts. Through this consolidation and mediation, the government as the guarantor of law and justice or what we can call a mediator can map the point of origin of the conflict, the actors involved, the magnitude of the losses, as well as the strategies and tactics for resolving it.